The Impact of Using Online Educational Tools on Science Learning among Students - Morteza Bakhtiarvand (Randwick International of Education and Linguistics Science Journal, 2020)
The present study aims to investigate the effect of using online educational tools on science learning among male students in the fifth year of primary school in Shahriyar city. Research method is semi-experimental based on pre-test - post-test design. All male students in the six year of primary school at Shahriyar city in the academic year 2016-17 that 260 of them were selected by random sampling. First, pages from the book of science without the use of educational tools in all classes are taught and filled researcher-made inventory of science learning (reliability of learning inventory using Cronbach's alpha coefficient was calculated and was used to assess the validity of the content from the point of view of primary school teachers and professors and experts). Then other pages of the math book using educational tools in 5 sessions of 30-minute was done supervised by teachers and researchers for all classes. Having the project been completed, researcher-made learning questionnaire was again conducted equal to the first questionnaire for all classes. And to analyze the assumptions, gamma test in agreement tables and non- parametric Spearman correlation test using SPSS software version 20 was conducted. The results showed that the active use of educational tools leads to a significant difference in science learning in students.